Transition metal imido compounds as Ziegler-Natta olefin polymerisation catalysts - Bolton, P; Mountford, P (2005)
Transition metal imido compounds having the general formula [(L) nM(NR)] [where (L) n is a supporting ligand or ligand set, and R typically is alkyl or aryl] have been known for nearly 50 years, and during the last two decades have been the focus of considerable attention. Relatively recently their potential application in the Ziegler-Natta polymerisation of olefins has been realised. In this contribution we review the Ziegler-Natta polymerisation of olefins by transition metal imido compounds. A general introduction to homogeneous Ziegler-Natta olefin polymerisation and key aspects of transition metal imido chemistry is given, followed by a short description of a related imido-based polymerisation process, namely ring-opening olefin metathesis polymerisation catalysed by imido-supported molybdenum and tungsten alkylidenes. A summary of the "design principles" that have been employed in the development of certain imido-based Ziegler-Natta catalysts is presented, followed by a comprehensive survey of the literature in the title area. © 2005 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.